Tropistry: A registry-based modular platform to improve care of neglected tropical diseases in nonendemic settings—Study protocol with two targeted conditions: acute schistosomiasis and cutaneous/mucocutaneous leishmaniasis - Carlos Bea-Serrano; Sami Alcedo; Nicole Berens-Riha; Saskia van Henten; Johan van Griensven; Steven Van Den Broucke; Patrick Soentjens; Federico Gobbi; Emmanuel Bottieau (PLoS ONE, 2025)
Background Neglected tropical diseases (NTDs) are increasingly encountered in nonendemic settings due to migration, international travel, and global mobility. Their clinical management is often challenging: evidence from endemic regions is limited or not directly applicable, and healthcare providers are frequently unfamiliar with their diagnosis and treatment. Consequently, there is substantial heterogeneity in diagnostic workup, therapeutic choices, and follow-up strategies, which may affect patient outcomes and complicate guideline development. Given the sporadic presentation of these diseases across individual centers and the overall low caseload in nonendemic settings, conducting randomized controlled trials to define optimal strategies is largely unfeasible. To address these gaps, we designed Tropistry, a modular, multicenter registry that integrates harmonized data collection with embedded expert-informed clinical guidance. Methods Tropistry is an ambispective, multicenter registry planned for implementation across Belgian and European sites. Its modular structure will allow the sequential integration of disease-specific components, initially focusing on acute schistosomiasis and cutaneous/mucocutaneous leishmaniasis (CL/MCL), selected for their sporadic occurrence, clinical complexity, and lack of standardized management. Data will be collected through REDCap-based electronic case report forms aligned with up-to-date, evidence-based recommendations to ensure harmonized and comparable data collection. Embedded expert-informed guidance will support clinicians unfamiliar with these diseases, complemented by expedited access to ITM experts via TROPmail and aggregated feedback through an interactive R Shiny-based dashboard. A structured evaluation framework will assess feasibility, usability, data quality, user engagement, and treatment adherence to ensure the platform’s utility and validity. Expected impact By centralizing harmonized data on diagnostic and therapeutic practices, Tropistry aims to address critical knowledge gaps in managing NTDs in nonendemic settings. For the initial targeted conditions, it will help clarify optimal strategies, such as the combination of corticosteroids and praziquantel for acute schistosomiasis and best practices for therapy and follow-up in CL/MCL. Beyond data collection, Tropistry will provide embedded expert-informed guidance, interactive dashboards, and direct access to ITM experts to support clinicians and promote standardized care. Its modular design will enable expansion to other challenging NTDs, while the built-in evaluation framework ensures continuous assessment and optimization of feasibility, usability, and clinical utility. Ultimately, Tropistry seeks to strengthen collaboration between reference centers and non-specialized facilities and generate robust real-world evidence to inform clinical practice, guideline development, and future trials.